COMPARATIVE ANALYSIS OF THE STORIES "YESTERDAY" BY NURALI KABUL AND "THE POET" BY FAZIL ISKANDER - Нематжонова Нафиса Боходировна; Эркузиева Маржона (Bright Mind Publishing, 2025)
The article provides a comparative analysis of the stories of the Uzbek writer Nurali Kabul "Yesterday" and the Abkhaz author Fazil Iskander "The Poet". The research is aimed at identifying common and different artistic principles of the two writers, belonging to different national literatures, but united by a common humanistic worldview. moral choice and the role of the individual in the socio-cultural context. The author comes to the conclusion that the works of Kabul and Iskander demonstrate similarities in the desire to assert the value of spiritual freedom and moral purity of a person.
Keywords: Nurali Kabul, Fazil Iskander, comparative analysis, story, memory, poetics, humanism, morality, artistic world.